Concomitant progressive multifocal leucoencephalopathy and primary central nervous system lymphoma expressing JC virus oncogenic protein, large T antigen. Issue 5 (1st October 2001) - Gallia, G L; Del Valle, L; Laine, C; Curtis, M; Khalili, K
Abstract : This report describes the concomitant occurrence of the JC virus (JCV) induced demyelinating disease progressive multifocal leucoencephalopathy (PML) and a primary central nervous system lymphoma (PCNS-L) in a patient with AIDS. Postmortem neuropathological examination revealed characteristic features of PML including multiple lesions of demyelination, enlarged oligodendrocytes with hyperchromatic nuclei (many containing eosinophilic intranuclear inclusions), and enlarged astrocytes with bizarre hyperchromatic nuclei. Immunohistochemical analysis demonstrated the expression of the JCV capsid protein VP-1 in the nuclei of infected oligodendrocytes and astrocytes. The PCNS-L lesion located in the basal ganglia was highly cellular, distributed perivascularly, and consisted of large atypical plasmacytoid lymphocytes. Immunohistochemical examination of this neoplasm identified it to be of B cell origin. Moreover, expression of the JCV oncogenic protein, T antigen, was detected in the nuclei of the neoplastic lymphocytes. This study provides the first evidence for a possible association between JCV and PCNS-L.